Publicidade em odontologia: avaliação dos aspectos éticos envolvidos - Garbin, Artênio José Isper [UNESP]; Orenha, Eliel Soares [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Gonçalves, Patrícia Elaine [UNESP] (My University, 2010)
Objective: To verify whether the professionals who make use of advertising in Dentistry by means of billboards respect the ethical aspects determined by the Federal Council of Dentistry Resolution No 71, 2006. Methods: This was an observational study in which 178 billboards of dental clinics in the municipality of São Paulo were assessed. Results: Among the billboards analyzed, 91.4% belonged to private persons and 9.6% to corporate bodies. With regard to the ethical aspects related to the advertisement, only 44.9% of the billboards presented all the mandatory items in accordance with the Federal Council of Dentistry. The item found the least number of times in the advertisements was the registration number in the Regional Council of Dentistry (34.8%). Among the items allowed by the Federal Council of Dentistry, the telephone number (65.2%) was the most commonly found. Among the ethical infractions, 1.7% of the billboards advertised the terms of payment. Conclusion: Professionals are not following the ethical precepts established by the Code of Ethics in Dentistry, and awareness of these professionals needs to be aroused, so that information about their services is communicated and divulged in an ethical manner.

Objetivo: Averiguar se os profissionais que fazem uso de publicidade em odontologia por meio de placas de anúncio respeitam os aspectos éticos determinados pela Resolução Conselho Federal de Odontologia n.71 de 2006. Métodos: Trata-se de um estudo observacional, no qual foram avaliadas 178 placas de anúncio de clínicas odontológicas no município de São Paulo. Resultados: Dentre as placas analisadas, 91,4% eram de pessoas físicas e 9,6% jurídicas. Em relação aos aspectos éticos relacionados ao anúncio, apenas 44,9% das placas apresentavam todos os itens obrigatórios, segundo o Conselho Federal de Odontologia. O item menos encontrado nas propagandas foi o número de inscrição no Conselho Regional de Odontologia (34,8%). Sobre os outros itens permitidos pelo Conselho Federal de Odontologia, o telefone (65,2%) foi o mais presente. Dentre as infrações éticas, foram observados que 1,7% das placas apresentavam a forma de pagamento. Conclusão: Os profissionais não estão seguindo os preceitos éticos estabelecidos no Código de Ética em Odontologia, sendo necessária a conscientização desses profissionais para que a comunicação e divulgação de seus serviços sejam realizados eticamente.
Publicity in dentistry: assessment of the ethical aspects involved
Keywords: Legislation dental; Marketing; Dentistry; Legislação odontológica; Marketing; Odontologia